Humane Leadership in Islamic Approaches - Mohd Faridh Hafez Mhd Omar (IntechOpen Limited, United Kingdom, 2024)
A leadership style that meets the interests thus ensures the sustainable development of humanity would be a key factor in the current disruptive world. Leadership in Islam prioritizes human values and that becomes a founding principle as stated in the Qur’an and the hadith of the Prophet Muhammad (peace be upon him). Using a descriptive method from previous studies, this study found that three issues would make the country a failed state. Prior to that, a leadership that values humanity is identified as a new approach that deserves attention as it was shown successfully through the leadership of Prophet Muhammad (peace be upon him). Such approaches were proven in the following events: 1) to make peace between communities; 2) recognizing the right to life and prohibiting murder; 3) no coercion in religion and social problems; and 4) da’wah activities which are inviting to goodness and forbidding evils. This study concludes that humane leadership that incorporates with fundamental principles of Islam while upholding the universal values of humanity should lead a new narrative in the current disruptive world.